PELATIHAN PRODUK DAUR ULANG SAMPAH PLASTIK - Nadia Asandimitra Haryono; Nindria Untarini (Dedication : Jurnal Pengabdian Masyarakat, 2018)
Awareness of residents in Griya Taman Asri related to waste segregation isnot yet optimal. On average, each household produces more than 1 cubic of disposal per day with 60% organic waste and 40% inorganic waste and garbage disposal is still mixed between organic and non-organic waste. This condition indicates that there is less awareness of the residents in sorting both the waste. Therefore, how to sort waste into organic waste and inorganic waste is the main problem to be solved. The problem of separating organic and inorganic waste can be solved if the residents' behavior in the housing complex in dealing with waste changes. In order for residents in the housing complex to change, it is necessary to create something that will stimulate citizens to change; the attractiveness offered is the economic value of waste. Recycling plastic bag into plastic bag craftis actually a good attraction and if continued and managed as a business unit, the more the economic appeal so that later will also impact on the incomes of citizens. Methods of this activity by using training of plastic waste recycling products. Data collection techniques used observation, interviews, and questionnaires. The data collected were analyzed descriptively using percentage technique.